ABOUT POSSIBILITY OF SOLAR ACTIVITY INFLUENCE ON CROP YIELD IN POLTAVA REGION - Писаренко, П. В.; Хлебнікова, Я. О. (Scientific Progress & Innovations, 2015)
The role of solar activity in the formation of yield of different crop in agroecology conditions in Poltava region is considered in this article. Data of crop yield in 25 districts of Poltava region for 47-years period (from 1966 to 2012) and data of average month solar activity (numbers of Wolf) during similar period are analyzed. It has been found out that maximum of solar activity and maximum of yield for all crops are coincided in 1989 and 1990. It has been established that phase of yield maximum displacement in comparison with solar activity maximum are carried from 1980 to 1973-78. It has been stressed that high indices of crop yield can be caused by solar activity maximums. Correlation analysis for each solar activity cycle between yield indices and average month numbers of Wolf during vegetation period is also carried out.